Anticancer Effects of Dihydroartemisinin on Human Esophageal Cancer Cells In Vivo - Cailing Jiang; Shumin Li; Yanjing Li; Yuxian Bai (Analytical Cellular Pathology)
Despite recent advances in chemotherapy and surgical resection, the 5-year survival rate of esophageal cancer still remains at the low level. Therefore, it is very important to discover a new agent to improve the life expectancy of patients with esophageal cancer. Dihydroartemisinin (DHA), a semisynthetic derivative of artemisinin, has recently exhibited promising anticancer activity against various cancer cells. But so far, the specific mechanism remains unclear. We have previously demonstrated that DHA reduced viability of esophageal cancer cells in a dose-dependent manner in vitro and induced cell cycle arrest and apoptosis. Here, we extended our study to further observe the efficacy of DHA on esophageal cancer cells in vivo. In the present study, for the first time, we found that DHA significantly inhibits cell proliferation in xenografted tumor compared with the control. The mechanism was that DHA induced cell apoptosis in both human esophageal cancer cell lines Eca109 and Ec9706 in vivo in a dose-dependent manner. The results suggested that DHA was a promising agent against esophageal cancer in the clinical treatment.